1956: the tripartite aggression - Bennafla, Karine (CNRS Éditions, 2023)
1st January25 March26 July29 October5 NovemberEnd of the Anglo-Egyptian Condominium of the SudanClosure of the British base at MoascarNationalisation of the Suez CanalIsraeli invasion of the SinaiLanding of Franco-British forces1956 was a crucial year in the contemporary history of the country. It featured the adoption of a new constitution by referendum, during which women voted for the very first time, Gamal Abdel Nasser’s accession to the presidency, the withdrawal of the last British troops...